Machine Learning Algorithms for Prediction of Permanent Pacemaker Implantation After Transcatheter Aortic Valve Replacement. (9th March 2021) - Tsushima, Takahiro; Al-Kindi, Sadeer; Nadeem, Fahd; Attizzani, Guilherme F.; Elgudin, Yakov; Markowitz, Alan; Costa, Marco A.; Simon, Daniel I.; Arruda, Mauricio S.; Mackall, Judith A.; Thal, Sergio G.
Abstract : Supplemental Digital Content is available in the text.